Developing a Security Software for Android-based Systems (Secand) - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2014)
In this study, an application has been developed in the Eclipse environment for android that is used to locate the stolen mobile devices with turned on status. If an user send a Short Message Service (SMS) to our device from another phone as soon as we notice that our device is stolen, the designed application, which the name of Secand was given by us, will detect the password within this SMS and understand that our phone is stolen. Our application must be continuously running in the background in order to detect this incoming SMS. After our application detects the password within SMS, it will retrieve Global Positioning System (GPS) coordinates of our device and send these coordinates to us via SMS. Secand must have all GPS and SMS related authorizations for all of these operations. If it is assumed that the thief is on the move after the first GPS coordinates are sent, our application must send the coordinates of device in certain frequencies. This range of time can be set by the user. Such details can be activated optionally by the user after Secand application is installed to the device.
Keywords: Security for Android; Retrieving GPS Coordinates; Reading SMS; Secand; DESIGN; TOOL